(untitled) (The Research of Medical Science Review, 2025)
The unmet need for family planning remains a pivotal challenge in global public health, particularly in low- and middle-income countries (LMICs). This article delves into the intricate socio-cultural, economic, and systemic barriers contributing to this phenomenon, with a specific focus on reproductive-aged women (15-49 years) at the gynecology ward of PUMHSW Nawabshah, Sindh. Leveraging quantitative and qualitative insights, the study underscores the imperative for transformative policies and culturally sensitive interventions to bridge the gap between family planning intentions and contraceptive use.